APPLICATION OF DIGITAL TECHNOLOGIES FOR THE STUDENTS WITH DIVERSE SKILLS DURING COVID:19 - Arshi Naim (American Journals Publishing, 2022)
This research was to confer suggestions on how Electronic tools in learning management services could be implemented by the instructors in the process of Learning and Teaching (LT) to meet the requirements of different learners in Information Systems (IS). In this study the module chosen was Marketing Management in Information System’s environment. We used Thurstone scale to measure the effectiveness of various electronic tools available on Learning Management Services (LMS) “Blackboard”. We also compared these electronic tools for their effectiveness in meeting learning outcomes for different learners in IS. For measuring assessments’ results, three tools were used namely Electronic-Quiz (EQ), Discussion Forum (DF) and Safe Assignment (SA). We also tried to measure the effectiveness of a new tools introduced on Blackboard named as Safe Assignment for submitting the assignment. Through this tool instructors were able to identify the percentage of plagiarism or matching between the peers. Based on three assessments’ results namely EQ, DF and SA, samples were categorized under best, average and poor. These assessments were considered for the purpose of study because they were conducted by the implementation on electronic tool LMS. The performance of student in each group was analyzed and it was found that students in all the groups could contribute and learn the best through open DF. Best Students tried to learn equally through all tools but other two groups plant least efforts and submitted their assignments using search engines such as Google.
Keywords: Electronic tool; LMS; Blackboard